The multidrug transporter ABCG2: still more questions than answers - Horsey, Aaron J.; Cox, Megan H.; Sarwat, Sunehera; Kerr, Ian D. (Portland Press Ltd, 2016)
ABCG2 is one of at least three human ATP binding cassette (ABC) transporters which can facilitate the export from cells of a wide range of chemically unrelated drug molecules. This capacity for multidrug transport is not only a confounding factor in chemotherapy, but is also one of the more perplexing phenomena in transporter biochemistry. Since its discovery in the last decade of the 20th century much has been revealed about ABCG2's localization, physiological function and its broad substrate range. There have also been many investigations of its structure and molecular mechanism. In this mini review article we take a Rumsfeldian approach to ABCG2 and essentially ask what we do know about this transporter, and what we will need to know about this transporter if we wish to use modulation of ABCG2 activity as a therapeutic approach.